Faktor-Faktor yang mempengaruhi pemberian ASI eksklusif pada Ibu menyusui di Kota Bengkulu tahun 2024 - oktaviani, dinda oktaviani (Poltekkes Kemenkes Bengkulu, 2025)
According to data from the World Health Organization (WHO), only 44% of babies under 6 months of age receive exclusive breast milk.. in the city of Bengkulu there are still mothers who do not give exclusive breast milk. 31% of this occurs due to maternal problems in breastfeeding such as breast milk dams, breast milk not smooth, mastitis, and the presence of other factors. The aim of the research is to determine the factors that influence exclusive breastfeeding in breastfeeding mothers in Bengkulu City. This type of research is descriptive analytical research with a cross-sectional research design approach. The population in this study was all 266 breastfeeding mothers in the city of Bengkulu, using a purposive sampling technique. The results of the study showed that the majority of respondents did not carry out breast care 66.0%, the majority of respondents with incorrect breastfeeding techniques 57.0%, the majority of respondents with sore nipples 61.0%, the majority of respondents 54.0% did not provide Exclusive breastfeeding 63.0%. The results of the bivariate analysis test showed that the p-value = ≤ α 0.05 means that it is significant, so Ho is rejected and Ha is accepted, which shows that there is a significant relationship between breast care, breastfeeding techniques and sore nipples with exclusive breastfeeding for breastfeeding mothers in Bengkulu City. Multivariate analysis of the most dominant factor was sore nipples. It is recommended that MCH program holders provide more interesting, innovative material regarding mothers' knowledge of the importance of breast care and breastfeeding techniques to prevent sore nipples, so that breast milk production during exclusive breastfeeding is fulfilled. Keywords: Exclusive breastfeeding, breast care, breastfeeding techniques, sore nipples